Indigenous Concepts of Gender, Communication and their Link to Spatial Processes: A Case of Kasepuhan Ciptagelar, Indonesia - Vidi Sukmayadi; M. Fasha Rouf; azizul halim yahya (LPPM Stikosa - AWS, 2023)
Cultural factors arguably are significant concerning how humans, thoughts, and products progress and organize spatially. In terms of indigenous people, they carry a symbol of irreplaceable diversity where men and women have different gender roles and responsibilities compared to contemporary communities. Hence, this paper attempts to explore the indigenous understandings of gender in one of the most distinctive indigenous communities in Indonesia, known as Kasepuhan Ciptagelar. The authors conducted a qualitative case study to investigate how spatial processes are linked to gender identities and activism in the community. The Findings show that the traditional community has implemented a form of gender equity, unlike the standard practice in modern Indonesian society. The concept of gender equity was established and communicated for generations as a form of social cooperation as a result of a geographical process where natural factors notably shaped their day to day life